ANALISA TINGKAT KERUSAKAN JALAN MENGGUNAKAN METODE PCI (PAVEMENT CONDITION INDEX) DAN APLIKASI SISTEM INFORMASI GEOGRAFIS PADA RUAS JALAN SANGA SANGA - DONDANG - NUR, ALFIAN (KURVA S JURNAL MAHASISWA, 2020)
Road damage that occurs in various areas, especially in the Sanga Sanga - Dondang area, Kutai Kartanegara Regency is a very complex problem and the losses suffered are quite large, especially for road users, such as long travel times and traffic accidents. The cause of road damage that occurs in the Sanga Sanga - Dondang road section is the burden of excessive traffic (overloaded) and the slow handling of existing damage so that it becomes more severe. The method used in this survey is a method of visual analysis based on the Pavement Condition Index (PCI) method. The Pavement Condition Index (PCI) method is used to identify damage to the road surface based on the survey results, so that appropriate and efficient handling of repairs can be identified in the study. the Sanga Sanga - Dondang road section and the Geographic Information System (GIS) application function to facilitate the presentation of damage information in the form of maps. The most dense damage to the Sanga Sanga - Dondang Sta 0 + 000 - 18 + 000 road segment, especially in segments 1 to 11, Potholes, Alligator cracking, Weathering, Edge cracking and Patching. The average pavement condition index (PCI) value of the Sanga Sanga - Dondang road section is 33% based on the existing classification, the road segment is classified as poor (Poor) and refers to the PCI matrix for Class I Arterial Roads, the road needs to be done. reconstructed.